Identifying Sustainability and Knowledge Gaps in Socio-Economic Pathways Vis-à-Vis the Sustainable Development Goals - Caroline Zimm; Frank Sperling; Sebastian Busch (Economies, 2018)
With the Sustainable Development Goals (SDGs), the global community has set itself an ambitious development agenda. Current analytical and quantitative modeling capabilities fall short of being able to capture all 17 SDGs and their targets. Even highly ambitious and optimistic pathways currently used in research, such as SSP1/SSP1-2.6, do not meet all SDGs (sustainability gaps) and fail to provide information on some of them (knowledge gaps). We show that for research and modeling purposes, the SDG targets can serve as a basis but need to be operationalized to reduce complexity and also to account for long-term sustainability concerns beyond 2030. We have explored here the requirements for assessing more comprehensively the sustainability of development pathways, guided by holistic interpretation of the SDGs to enable an assessment of the potential embedded synergies and trade-offs between the economic, social and environmental objectives. We see this as call for action for science to work on filling these gaps. At the same time, this is also a call for policy makers and the global community to close the sustainability gaps that emerge from such analysis. We anticipate that such analysis will provide useful information for policy advice and investment decisions during implementation of the UN 2030 Agenda.